Surface Integrity at Reaming Operation by MT3 Head - Kouril, Karel; Cep, Robert; Janasek, Adam; Kriz, Antonin; Stancekova, Dana (Manufacturing Technology Journal, 2014)
Surface integrity reflects the properties of a material after it has been subject to some type of manufacturing process or modification during machining process and surface integrity can also have a great impact on a parts function. The changes limit the component quality or in the same cases performed the surface as an unacceptable. It has long been known that the method of surface finishing and combination of surface roughness, residual stress, cold work, or phase transformations strongly influence the service performance of manufactured parts as fatigue or corrosion. The main aim of the article is testing a high-productive reaming tool type MT3 with respect to different values of tool-life because holes making among the most important operation in machining and one of the most common in drilling operation.
Keywords: Machining; Surface Integrity; Reaming; Testing